The Spanish notarial divorce in the light of the Court of Justice of European Union - Rodríguez Vázquez, Mª Ángeles (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
In the Judgment of 15 November 2022, in case C-646/20, Senatsverwaltung für Inneres und Sport, Standesamtsaufsicht, the Court of Justice of the European Union establishes that the dissolution of a marriage on the basis of Article 12 of Italian Decree-Law No 132/2014 constitutes a “judgment” within the meaning of article 2 of Regulation 2201/2003. The Court interprets the two elements that must be met for a non-judicial divorce decision to be considered a “judgment”. This paper analyzes how these elements are fulfilled in the Spanish notarial divorces and the new rules of the Regulation 2019/1111 on recognition and enforcement of authentic instruments and agreements.
Keywords: non judicial divorce; judgment; recognition; Regulation 2201/2003; Regulation 2019/1111